The psychology of strength and conditioning - Tod, David; Lavallee, David, 1969- (London : Routledge, 2012)
'An effective strength and conditioning program underpins the training regime of every successful athlete or sportsperson and it is now widely recognised that psychology plays a significant role in the application of strength and conditioning principles. This is the first book to examine the importance of psychological factors in strength and conditioning and to offer a comprehensive overview of current research, theory and best practice. Written by a team of leading international researchers and practitioners, the book looks at how psychology influences training and performance and how training can influence an individual's psychological well-being. It explores a range of key topics in contemporary sport psychology and athletic training, including: mental skills training behaviour change psychology in professional practice psychological problems, including exercise dependence, eating disorders and steroid use Throughout, the book combines evidence-based research with discussion of the practical issues facing athletes, coaches and sport science professionals. By firstly developing our understanding of the latest psychological skills and techniques used by athletes and coaches to maximise strength and conditioning training and performance, and then the ways other psychological factors influence, and are influenced by, strength and conditioning training, this book represents invaluable reading for all advanced students, researchers, trainers and sport scientists with an interest in strength and conditioning or sport psychology'--
Keywords: Physical fitness -- Psychological aspects; Sports -- Psychological aspects; Muscle strength